2013
DOI: 10.1073/pnas.1306390110
|View full text |Cite|
|
Sign up to set email alerts
|

BslA is a self-assembling bacterial hydrophobin that coats the Bacillus subtilis biofilm

Abstract: Biofilms represent the predominant mode of microbial growth in the natural environment. Bacillus subtilis is a ubiquitous Gram-positive soil bacterium that functions as an effective plant growth-promoting agent. The biofilm matrix is composed of an exopolysaccharide and an amyloid fiber-forming protein, TasA, and assembles with the aid of a small secreted protein, BslA. Here we show that natively synthesized and secreted BslA forms surface layers around the biofilm. Biophysical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
363
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(379 citation statements)
references
References 46 publications
15
363
0
1
Order By: Relevance
“…4,12 Our simulations provide reliable estimates of the adsorption free energy of wild-type (wt) BslA and enable us to rationalize a number of experimental observations.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…4,12 Our simulations provide reliable estimates of the adsorption free energy of wild-type (wt) BslA and enable us to rationalize a number of experimental observations.…”
mentioning
confidence: 77%
“…It has been shown previously that purified BslA 42−181 spontaneously aggregates into a stable protein film at air-water interfaces in vitro. 4 Electron microscopic images of the BslA film have demonstrated that the most stable assembly of BslA surface layers correlates with a high degree of order between individual proteins. 12 In our simulations, the outward facing conformation (wt-BslA-L out ) exhibits the most clearly defined upright orientation at the interface in combination with the highest adsorption free energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genes for fiber production (a three-gene operon consisting of tapA, sipW, and tasA) and EPS production (the 15-gene epsA-O operon) are held silent in growing, motile cells by the SinR and AbrB repressors but are derepressed during biofilm formation, leading to high-level production of the protein and polysaccharide components of the extracellular matrix (Chu et al 2006;Chai et al 2008). An additional component of the matrix, BslA, confers hydrophobicity on the biofilm (Kobayashi and Iwano 2012;Hobley et al 2013). Because mutants blocked in matrix production can be complemented extracellularly by matrix-producing cells (Branda et al 2001), the matrix can be thought of as a common good that is shared among cells in the community.…”
mentioning
confidence: 99%